Modelling the riskiness in country risk ratings - Hoti, Suhejla; McAleer, Michael (Amsterdam ; Boston : Elsevier, 2005)
Focussing on the rating system of the international country risk guide, this book analyses various univariate and multivariate risk returns and corresponding symmetric and asymmetric models of conditional volatility, as well as conditional correlations.
Includes bibliographical references and indexes.
oif 17/07/14
Loan
Keywords: Country risk -- Mathematical models. Economics &#x000A